Structural and Optical Properties of Pristine and Doped CsPbBr3 Perovskite. Issue 1 (March 2021) - Sharaf, Ibrahim M.; Shurukhina, Anna V.; Emeline, Alexei V.
Abstract: The influence silver substitution at 0%-5% on the fundamental absorption edge of CsPbBr3 perovskites was studied. Here we examine the optical performance (diffuse reflectance spectroscopy) from Ag-CsPbBr3 perovskites samples. The investigation of the powder X-ray diffraction (XRD) of the CsPbBr3 perovskites indicates that an orthorhombic-phase structure. Our results imply that Ag + ions serve as substitutional dopants to replace Pb 2+ ions in the perovskites. Photoluminescence (PL) and absorption studies show that no major changes are made in the perovskite bandgaps, and the charging transfers are facilitated with different molecular Ag donors at their interface. This work demonstrates monovalent doping's tunability on halide perovskites' optical properties, shedding light toward their prospective applications in varied optoelectronic devices.